Agency over technocracy: how lawyer archetypes infect regulatory approaches: the FCA example. (3rd July 2021) - Clark, Trevor; Moorhead, Richard; Vaughan, Steven; Brener, Alan
ABSTRACT: In this article, we look at the contested role of in-house lawyers in regulated organisations in the financial sector. A recent Financial Conduct Authority consultation on whether to designate the head of legal of banks, insurance companies and other financial firms as 'Senior Managers' and the decision which flowed from it, reflected a flawed view of lawyers as a neutral technocracy of mere legal technicians; we show how the FCA's decision is potentially damaging to the public interest and failed to take into account that in-house lawyers are often important decision-makers and influencers within their organisations. We put the case for an alternative view; that in-house lawyers are professionals, with agency that requires them to act in accordance with ethical norms and means they should be made more accountable for their conduct.